1992
DOI: 10.1007/bf00202315
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Al/Si disorder on the I $$\bar 1$$ -P $$\bar 1$$ Co-Elastic phase transition in Ca-rich plagioclase

Abstract: Abstract. The influence of A1/Si disorder in the anorthite tetrahedral framework upon the I1-P1 displacive transition of that framework has been investigted at high-temperatme by powder X-ray diffraction. The temperaturedependence of the order parameter in a heat-treated (disordered) anorthite and a Ca-rich plagioctase has been determined from spontaneous strain measurements. Both samples show appreciable disorder, with Qoa = 0.88 in both cases. In each, the critical exponent/~ appears to be intermediate betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Different order parameters of the investigated samples are reported in Table 2. The spontaneous strain, also called lattice strain, relating to the I1-P1 transition decreases with decreasing Al-Si order and Ca content (Redfern et al 1988;Redfern 1992). We infer that decreasing Al-Si order and Ca content provides an explanation for the origin of the structural fl uctuations in the synthetic An 100 , An 92 Ab 8 , and An 85 Ab 15 samples.…”
Section: Structural Fl Uctuations In Plagioclasementioning
confidence: 78%
See 1 more Smart Citation
“…Different order parameters of the investigated samples are reported in Table 2. The spontaneous strain, also called lattice strain, relating to the I1-P1 transition decreases with decreasing Al-Si order and Ca content (Redfern et al 1988;Redfern 1992). We infer that decreasing Al-Si order and Ca content provides an explanation for the origin of the structural fl uctuations in the synthetic An 100 , An 92 Ab 8 , and An 85 Ab 15 samples.…”
Section: Structural Fl Uctuations In Plagioclasementioning
confidence: 78%
“…Decreases in Al-Si ordering results in decreases in the spontaneous strain connected with the I1-P1 transition and prevents the development of large c-and d-type domains (Redfern 1992).…”
Section: The C1-i1 Phase Transition and Q Odmentioning
confidence: 99%
“…In fully ordered anorthite the PI-I1 transition is tricritical (Redfern and . Salje 1987), but the addition of albite component and/or Si,A1 disorder decreases the transition temperature and causes a change to second-order behavior (Redfern and Salje 1987;Redfern et al 1988;Redfern 1992). At elevated pressures the PI-II transition is first-order and occurs near 2.5 GPa at room temperature for Si,A1 ordered anorthite (Angel et al 1989).…”
Section: Introductionmentioning
confidence: 93%
“…For a weak coupling between Ca and the framework, these authors estimate that the hopping rate of the Ca atoms between the split positions must be greater than about 6 kHz to give spectra consistent with Ii symmetry. Additional reviews of the experimental data for the anorthite P1 I1 transition are given by Van Tendeloo et al (1989), Redfern and Salje (1992), and Redfern (1992).…”
Section: Introductionmentioning
confidence: 99%
“…In-situ, HT TEM observations showed that dynamically fluctuating c-antiphase microdomains form at T > T c at the expense of the large, static, low-temperature domains (Van Tendeloo et al 1989). The transition is thermodynamically tricritical for well-ordered anorthite (Redfern andSalje 1987, 1992), but switches to second order in less-ordered samples (Redfern 1992) and in those with even a very slight amount of Na (0.02 atoms per formula unit, Redfern et al 1988). The transition is thermodynamically tricritical for well-ordered anorthite (Redfern andSalje 1987, 1992), but switches to second order in less-ordered samples (Redfern 1992) and in those with even a very slight amount of Na (0.02 atoms per formula unit, Redfern et al 1988).…”
Section: Introductionmentioning
confidence: 99%